2014
DOI: 10.5812/numonthly.22009
|View full text |Cite
|
Sign up to set email alerts
|

Restless Leg Syndrome: a Neglected Diagnosis

Abstract: Context:Restless legs syndrome (RLS) is an irresistible urge to move legs that usually occur during inactivity and at night. This neurologic condition is associated with increased risk of nocturnal hypertension as well as cardiovascular events and affects patient’s sleep, which leads to anxiety, depression, and decreases quality of life. Presence of RLS in patients on hemodialysis is associated with higher mortality rate. Most of the times, patients have indescribable symptoms. The aim of this review was to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
1
42
0
2
Order By: Relevance
“…In one of the studies, from Spencer and colleagues, it was concluded that this could be due to the fact that iron deficiency is insufficient by itself to be associated with RLS, as this disorder has a multifactorial derivation. Einollahi and Izadianmehr showed that apart from iron deficiency, old age, female sex, genetic background, and, being pregnant or having end‐stage renal disease contributed to the incidence of RLS. Another study by Didriksen and colleagues could not detect an association between reduced ferritin levels and likelihood of RLS in whole blood donors as well.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In one of the studies, from Spencer and colleagues, it was concluded that this could be due to the fact that iron deficiency is insufficient by itself to be associated with RLS, as this disorder has a multifactorial derivation. Einollahi and Izadianmehr showed that apart from iron deficiency, old age, female sex, genetic background, and, being pregnant or having end‐stage renal disease contributed to the incidence of RLS. Another study by Didriksen and colleagues could not detect an association between reduced ferritin levels and likelihood of RLS in whole blood donors as well.…”
Section: Discussionmentioning
confidence: 90%
“…The timing of filling in the questionnaires may have caused the varied results. For example, RLS symptoms were assessed in the 7 days before donation only, resulting in donors with infrequent RLS symptoms possibly being missed; or donors were invited to fill in a questionnaire about unpleasant RLS directly after donation, possibly leading to overreporting of RLS …”
Section: Discussionmentioning
confidence: 99%
“…One study showed that older individuals with RLS had low sleep quality, less sleep duration during weekdays, and difficulty initiating sleep compared with those without RSL (Safak et al, ). Awakened by the sensations, patients get out of bed to walk to relieve the symptoms during the night, which disrupts their sleep (Einollahi & Izadianmehr, ). In patients on hemodialysis with RLS, daytime sleepiness, insomnia, and low sleep quality were commonly reported when compared with those without RLS (Chavoshi et al, ).…”
Section: Restless Legs Syndrome or Willis‐ekbom Diseasementioning
confidence: 99%
“…Moreover, RLS may cause problems with the dialysis process (7). There are four main clinical criteria for the diagnosis of RLS according to the international restless leg syndrome study group (IRLSSG) including: 1, an urge to move legs that is usually associated with paresthesia; 2, alleviation of the symptoms by moving the legs; 3, aggravation or exacerbation of the symptoms particularly at rest or during sitting or lying down in the bed; and 4, worsening of the signs at night (8,9). The etiology of RLS is yet unknown.…”
Section: Introductionmentioning
confidence: 99%